C7MS4-C5MS3-containing phosphoaluminate cement-based steel bar protective coating material as well as preparation method and application of C7MS4-C5MS3-containing phosphoaluminate cement-based steel bar protective coating material
By using reinforced bar protective coating materials prepared with C7MS4-C5MS3 aluminate cement and modification additives, the problem of poor adhesion of existing coating materials is solved, and efficient corrosion protection and environmentally friendly results are achieved.
Patent Information
- Application Number
- CN202411570535.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-07-17
- Filing Date
- 2024-11-06
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-06
AI Technical Summary
The existing steel bar anti-corrosion coating materials have poor adhesion in humid and acid-base environments, making it difficult to protect steel bars stably for a long time, and the instability and potential environmental risks of nanomaterials exist.
Inorganic cementitious material containing C7MS4-C5MS3 aluminate cement as the matrix, combined with modification additives such as epoxy resin and styrene butadiene latex, a protective coating material with strong adhesion and easy-to-paint steel bars is prepared.
The coating material has good corrosion protection effect in a high concentration Cl-environment, strong adhesion, easy to apply, high stability, extends the service life of the steel bars, and does not release toxic gases, and is environmentally friendly.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to a C7MS4-C5MS3 phosphate aluminate cement-based steel bar protective coating material and a preparation method and application thereof, belonging to the technical field of civil engineering. Background Art
[0002] The steel bars in reinforced concrete structures bear the main load-bearing function. However, in a humid, acidic or alkaline environment, the steel bars are prone to corrosion, which in turn causes damage to the concrete structure. In order to extend the service life of the concrete structure and protect the steel bars from corrosion, steel bar anti-corrosion coating technology has emerged.
[0003] The development of steel bar anti-corrosion coating technology has gone through several stages. Initially, people used natural materials such as asphalt or paraffin to treat steel bars for corrosion protection. These materials have certain anti-corrosion effects, but they have problems such as poor adhesion and poor durability in long-term use. With the continuous advancement of science and technology, high-performance coatings such as synthetic resin coatings and epoxy resin coatings have gradually become mainstream, with good corrosion resistance and adhesion. However, the characteristics of the organic material itself as the main body make the coating construction relatively more complicated during use, with poor weather resistance and easy to be affected by environmental factors such as ultraviolet rays, high temperature, and humidity, resulting in aging, cracking or peeling of the coating, thereby affecting its anti-corrosion effect.
[0004] In recent years, steel bar anti-corrosion coating technology has also ushered in new developments. The application of nanotechnology has brought new possibilities to steel bar anti-corrosion coatings. By adding nanomaterials, the corrosion resistance and mechanical properties of the coating can be improved, and the service life of the anti-corrosion coating can be extended. However, its immature technology will bring instability to its materials, which may change during long-term use, resulting in a decline in its performance; and some nanomaterials may pose potential risks to the environment and human health. When using nanomaterials, sufficient risk assessments and safety measures are required to ensure that they will not cause harm to the environment and human body during construction and use. Inorganic phosphate aluminate coating materials have higher compatibility with concrete because of their own materials. As a coating, they have high stability and durability after being applied to steel bars. However, there is a problem that the inorganic phosphate aluminate coating has poor adhesion to steel bars and is not easy to apply. Summary of the invention
[0005] In view of the problems existing in the prior art, the present invention provides a C7MS4-C5MS3 phosphate aluminate cement-based steel bar protective coating material, which can effectively solve the problem of poor adhesion between phosphate coating and steel bars. This invention not only provides a strong guarantee for the long-term stable operation of concrete structures, but also promotes the continuous innovation and development of the architectural coatings industry.
[0006] The present invention also provides a method for preparing the above-mentioned C7MS4-C5MS3 phosphate aluminate cement-based steel bar protective coating material.
[0007] The present invention further provides an application of a C7MS4-C5MS3 phosphate aluminate cement-based steel bar protective coating material.
[0008] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions: The present invention provides a C7MS4-C5MS3 phosphate aluminate cement-based steel bar protective coating material, comprising the following components in parts by weight: Inorganic gelling material: 50-90 parts; Binder: 8-20 parts; Emulsion stabilizer: 1-10 parts; Early strength agent: 2-10 parts; Dispersant: 1-10 parts; Water reducing agent: 0.1-1 part; Water-to-cement ratio: 0.23 to 0.38 parts.
[0009] Furthermore, the inorganic gelling material includes the following components in parts by weight: Aluminophosphate cement containing C7MS4-C5MS3 mineral phase: 65-85 parts; Sulphoaluminate cement: 5-10 parts; Portland cement: 20-30 parts.
[0010] Furthermore, the aluminophosphate cement containing C7MS4-C5MS3 mineral phase comprises the following system and components:
[0011] Calcium phosphate aluminate C8A6P: 20-30%; Contains calcium aluminate phosphate C (A, P): 15-20%; Ca5(PO4)2SiO4: 20-25%; α-type Ca3(PO4)2: 1-10%; C4AF: 1-10%; C7MS4- C5MS3: 10-20%.
[0012] Furthermore, the C7MS4-C5MS3 mineral phase aluminophosphate cement comprises the following components: Fluorapatite: 15-20 parts: Low-grade bauxite: 30-50 parts; Low-grade limestone: 30-60 parts; Iron powder: 1-10 parts.
[0013] Furthermore, the binder is composed of one or more of epoxy resin, styrene-butadiene latex, vinyl acetate and ethylene copolymer rubber powder; preferably, the modulus of the binder is 1.0-10; most preferably, the mass ratio of epoxy resin, styrene-butadiene latex, vinyl acetate and ethylene copolymer rubber powder in the binder is 10-20:70-80:1-10.
[0014] Furthermore, the emulsion stabilizer is composed of one or two of phenolic resin and coumarone resin.
[0015] Furthermore, the dispersant is composed of one or more of sulfonate, fatty alcohol polyoxyethylene ether, and polyether polyol.
[0016] Furthermore, the early strength agent is composed of one or more of sodium sulfate, triethanolamine, calcium formate and urea.
[0017] The present invention also provides a method for preparing the above-mentioned C7MS4-C5MS3 phosphate aluminate cement-based steel bar protective coating material, comprising the following steps: 1) The fluorine-containing apatite, bauxite, low-grade limestone and iron powder are weighed, calcined at 1300-1500° C., rapidly cooled, crushed and sieved to obtain aluminophosphate cement containing C7MS4-C5MS3 mineral phases; 2) Mix the water reducing agent, dispersant, binder, early strength agent, emulsion stabilizer and water to obtain a mixed liquid; 3) Dry-mixing the inorganic gelling material; 4) Finally, the uniformly mixed inorganic gelling material and the mixed liquid are stirred thoroughly.
[0018] Another object of the present invention is to provide the application of the above-mentioned C7MS4-C5MS3 phosphate aluminate cement-based steel bar protective coating material in steel bar rust prevention.
[0019] The strong-bonding, easy-to-brush steel bar coating of the present invention uses C7MS4-C5MS3 phosphate aluminate cement, sulphoaluminate cement and silicate cement as a matrix, and uses a binder, an early strength agent, a water reducer, an emulsifier stabilizer and a dispersant as modification additives. The obtained rust-resistant coating has good bonding properties with steel bars and is easy to brush during the construction process.
[0020] Compared with the prior art, the present invention has the following beneficial effects: (1) The C7MS4-C5MS3 phosphate aluminate cement-based steel bar protective coating material of the present invention is based on C7MS4-C5MS3 phosphate aluminate cement, sulphoaluminate cement and silicate cement, and has excellent corrosion resistance and easy brushing performance. Under the synergistic effect of various raw materials, the coating material has good base adhesion, high mechanical strength, and improved coating brushing performance. The prepared rust-proof coating has high hardness, is easy to brush, has strong stability, good adhesion to steel bars, and has good corrosion protection effect in high concentration Cl-; the steel bar coating material prepared by the composite method of organic and inorganic materials can significantly improve the corrosion resistance of steel bars in reinforced concrete and extend the service life of steel bars.
[0021] (2) The present invention uses inorganic materials as basic materials, does not release toxic gases, and is environmentally friendly. Therefore, the strong-adhesive and easy-to-apply steel bar coating of the present invention has the development potential of green and pollution-free steel bar coating.
[0022] (3) The present invention also provides the use of a cement-based coating material containing C7MS4-C5MS3 phosphate aluminate in preventing steel bar rust. A coating with strong adhesion and easy brushing is applied to the surface of the steel bar to form an anti-rust coating. The protective coating material provided by the present invention, under the synergistic effect of various raw materials, helps to solidify Cl-, and helps to form a passivation film on the surface of the steel bar, further protecting the steel bar from rust. In addition, the coating provided by the present invention can form a viscous solution in water, which increases the overall viscosity of the coating or latex, helps to improve the adhesion of the coating and the adhesion of the latex; the coating has good brushing performance and fluidity, and has good stability. Implementation data show that in the case of a small amount of pitting corrosion on the coated steel bar, the remaining uncorroded parts are not affected, indicating that the coating of the present invention has a good bonding effect with the steel bar, and can effectively delay the corrosion process even when the coating is damaged; (4) The steel bar coating of the present invention is a protective coating that has a strong adhesion and is easy to apply and can improve the bonding strength between steel bars and concrete, and can also improve the fluidity of the coating during the construction process, making it easy to apply. DETAILED DESCRIPTION
[0023] The present invention provides a coating with strong adhesive force and easy to apply, which is prepared from raw materials including the following components: an inorganic gelling material and a modification auxiliary agent; The inorganic cementitious materials include: C7MS4-C5MS3 phosphate aluminate cement, sulphoaluminate cement, silicate cement; The modification aids include: binder, early strength agent, emulsion stabilizer, dispersant, water reducer; The binder includes: epoxy resin, styrene-butadiene latex, vinyl acetate and ethylene copolymer rubber powder; The early strength agent comprises: sodium sulfate, triethanolamine, calcium formate and urea; The emulsion stabilizer includes: phenolic resin, coumarone resin; The dispersant includes: sulfonate, fatty alcohol polyoxyethylene ether, polyether polyol; In the present invention, unless otherwise specified, the materials and equipment used are commercially available products in the art.
[0024] In the present invention, the mass ratio of C7MS4-C5MS3 phosphate aluminate cement, sulphoaluminate cement and silicate cement contained in the inorganic cementitious material is 50-90:1-10:10-30. The coating prepared by the coating obtained by the mass ratio can meet the corrosion protection requirements while ensuring the construction performance.
[0025] In the present invention, the inorganic gelling material reacts with the binder, and the addition of the emulsifier stabilizer can form a viscous solution in water, which increases the overall viscosity of the coating and helps to improve the adhesion of the coating and the adhesion of the latex; the addition of the emulsifier stabilizer can also improve the rheology of the coating or latex, prevent liquid separation and mutual precipitation, maintain the stability of the emulsion, make it easier to handle during the coating process, help to achieve more uniform coating and improve the adhesion of the coating; in addition, it can form a soft film layer during the drying process, increase the adhesion between the coating and the substrate, and the strong adhesion and easy-to-brush type coating is a steel bar coating material with unlimited development potential.
[0026] In the present invention, the adhesive is made of epoxy resin, styrene-butadiene latex, vinyl acetate and ethylene copolymer rubber powder.
[0027] In the present invention, the modulus of the adhesive is 1.0 to 10 In the present invention, the mass ratio of the epoxy resin, styrene-butadiene latex, vinyl acetate and ethylene copolymer rubber powder is 10-20:70-80:1-10.
[0028] In the present invention, the dosage of the emulsion stabilizer is preferably adjusted according to different coating methods, which include dipping, brushing or spraying. When the coating method is dipping and brushing, the fluidity and viscosity of the coating slurry are required to be relatively low, and the mass ratio of the emulsion stabilizer to the inorganic gelling material is preferably 0.01 to 0.1:1; when the coating method is spraying, the fluidity and viscosity of the coating slurry are required to be relatively high, and the amount of the emulsion stabilizer added can be appropriately increased to meet the construction requirements of spraying.
[0029] In the present invention, the water reducer is preferably a commonly used water reducer for concrete, and more preferably a polycarboxylic acid water reducer. The selected water reducer can adjust the fluidity of the coating, increase the plastic viscosity of the slurry, and facilitate construction and painting.
[0030] The present invention also provides a method for preparing the easy-to-brush steel bar coating with strong bonding force described in the above technical solution, comprising the following steps: Weigh and mix C7MS4-C5MS3 phosphate aluminate cement, sulphoaluminate cement and silicate cement in a certain proportion to obtain an inorganic cementitious material; The present invention has no special requirements on the mixing method and time, as long as a uniformly dispersed mixed powder is obtained.
[0031] The water reducing agent and deionized water are mixed, and then mixed with a binder, an early strength agent, an emulsifier stabilizer, and a dispersant to obtain the easy-to-brush steel bar coating with strong bonding strength.
[0032] In the present invention, the mixing method of the mixed powder and the modifying aid is preferably low-speed stirring with an orbital speed of 45 to 65 r / min, and then high-speed stirring with a rotation speed of preferably 120 to 140 r / min, so that the slurry is mixed evenly.
[0033] In the present invention, the curing preferably includes standard environment curing, and the parameters of the standard environment curing include: the curing temperature is preferably 25±0.5°C, the relative humidity is preferably 95±5%, and the curing time is preferably 28±2 days.
[0034] Example 1 (1) Weigh 75 parts of C7MS4-C5MS3 phosphate aluminate cement, 5 parts of sulphoaluminate cement and 20 parts of silicate cement, and mix them evenly to obtain an inorganic cementitious material; The composition of C7MS4-C5MS3 aluminophosphate cement is Calcium phosphate aluminate C8A6P: 28%; Contains calcium aluminate phosphate C (A, P): 18%; Ca5(PO4)2SiO4: 24%; α-type Ca3(PO4)2: 6%; C4AF: 4%; C7MS4-C5MS3: 20% (2) Weigh 90 parts of inorganic gelling material, 20 parts of binder (epoxy resin, styrene-butadiene latex, vinyl acetate and ethylene copolymer rubber powder in a mass ratio of 10:80:5), 10 parts of triethanolamine early strength agent, 0.3 parts of polycarboxylic acid water reducer, 10 parts of fatty alcohol polyoxyethylene ether dispersant, 5 parts of phenolic resin emulsion stabilizer, and a water-binder ratio of 0.3; (3) Wet-mix the C7MS4-C5MS3 phosphate aluminate cement, sulphoaluminate cement and silicate cement in a polytetrafluoroethylene tank, and then dry them in an oven at 80°C. After drying, grind and sieve them; (4) Add the water reducing agent to the deionized water weighed in step 1), mix and let stand; (5) Place the binder, emulsifier stabilizer, early strength agent and dispersant in a stirrer, add to the liquid obtained in step 3), stir at low speed for 3 min, and the speed is 45±3r / min. Then add the inorganic gelling material mixed powder prepared in step 2), stir at low speed for 2 min, let stand for 90s, and stir at high speed for 2 min, the low speed is 120±10r / min, the high speed is 280±10r / min, and the high speed is 10000rpm to obtain an easy-to-brush adhesive steel bar coating.
[0035] Example 2 The material composition is: 90 parts of inorganic gelling material (the composition is the same as in Example 1), 15 parts of binder (the mass ratio of epoxy resin, styrene-butadiene latex, vinyl acetate and ethylene copolymer powder is 10:70:10), 8 parts of triethanolamine early strength agent, 0.3 parts of polycarboxylic acid water reducer, 10 parts of fatty alcohol polyoxyethylene ether dispersant, 5 parts of phenolic resin emulsion stabilizer, and water-binder ratio of 0.3.
[0036] The preparation method is the same as that of Example 1.
[0037] Example 3 The material composition is: 90 parts of inorganic gelling material (the composition is the same as in Example 1), 20 parts of styrene-butadiene latex binder, 10 parts of triethanolamine early strength agent, 0.3 parts of polycarboxylic acid water reducer, 10 parts of fatty alcohol polyoxyethylene ether dispersant, 5 parts of phenolic resin emulsion stabilizer, and a water-cement ratio of 0.3.
[0038] The preparation method is the same as that of Example 1.
[0039] Example 4 (1) Weigh 65 parts of C7MS4--C5MS3 phosphate aluminate cement (with the same composition as in Example 1), 5 parts of sulphoaluminate cement, and 30 parts of silicate cement, and mix them evenly to obtain an inorganic cementitious material; (2) Weigh 90 parts of inorganic gelling material, 20 parts of binder (same composition as in Example 1), 10 parts of triethanolamine early strength agent, 0.3 parts of polycarboxylic acid water reducer, 10 parts of fatty alcohol polyoxyethylene ether dispersant, 5 parts of phenolic resin emulsion stabilizer, and a water-binder ratio of 0.3; The rest is the same as in Example 1.
[0040] Example 5 (1) Weigh 70 parts of C7MS4-C5MS3 phosphate aluminate cement, 10 parts of sulphoaluminate cement and 20 parts of silicate cement, and mix them evenly to obtain an inorganic cementitious material; (2) Weigh 90 parts of inorganic gelling material, 20 parts of binder (same composition as in Example 1), 10 parts of triethanolamine early strength agent, 0.3 parts of polycarboxylic acid water reducer, 10 parts of fatty alcohol polyoxyethylene ether dispersant, 5 parts of phenolic resin emulsion stabilizer, and a water-binder ratio of 0.3; The rest is the same as in Example 1.
[0041] Comparative Example 1 (1) Weigh 75 parts of ordinary phosphate aluminate cement not containing C7MS4-C5MS3, 5 parts of sulphoaluminate cement, and 20 parts of silicate cement, and mix them evenly to obtain an inorganic cementitious material; (2) Weigh 90 parts of inorganic gelling material, 20 parts of styrene-butadiene latex binder, 10 parts of triethanolamine early strength agent, 0.3 parts of polycarboxylic acid water reducer, 10 parts of fatty alcohol polyoxyethylene ether dispersant, 5 parts of phenolic resin emulsion stabilizer, and a water-to-binder ratio of 0.3.
[0042] The other steps are the same as those in Example 1, and a cement-based steel bar protective coating material free of C7MS4-C5MS3 phosphate aluminate is obtained.
[0043] Application Example 1 After forming, the two coatings prepared in Example 1 and Comparative Example 1 were placed in a carbonization test box, and carbonization depth tests were performed after 90 days and 180 days. The comparative test results of the two coatings are as follows: Table 1
[0044] Application Example 2 The experiment used 12mm hot-rolled ribbed steel bars commonly used in construction, model HRB400. The steel bars were firstly treated with rust removal and oxide layer removal, and then weighed.
[0045] The coatings prepared in Implementations 1 to 3 were applied to the steel bar surface. The coatings were all applied by brushing. After hardening, they were wrapped with a layer of plastic wrap and placed in a standard curing room for curing. The curing time was 3 days, 7 days, and 28 days, respectively. After the curing time was over, the steel bar coatings in Examples 1 to 3 were obtained. Electrochemical corrosion tests were performed on the steel bar coatings to calculate Cl - The specific results are shown in Table 2.
[0046] Table 2 Curing Cl of samples at different ages - performance
[0047] Application Example 3 The experiment used 12mm hot-rolled ribbed steel bars commonly used in construction, model HRB400. The steel bars were firstly treated with rust removal and oxide layer removal, and then weighed.
[0048] The coatings prepared in Implementation 1, 4-5 were applied to the steel bar surface, and the coatings were all applied by brushing. After hardening, they were wrapped with a layer of plastic wrap and placed in a standard curing room for curing. The curing time was 3d, 7d, and 28d, respectively. After the curing time was over, the steel bar coatings in Implementation 1, 4-5 were obtained. The steel bar coatings were tested for bonding strength, and the specific results are shown in Table 3.
[0049] Table 3 Bond strength of different coating base materials of the sample in the example
Claims
1. A C7MS4-C5MS3 phosphate aluminate cement-based steel bar protective coating material, characterized in that: The composition comprises the following components in parts by weight: Inorganic gelling material: 50-90 parts; Binder: 8-20 parts; Emulsion stabilizer: 1-10 parts; Early strength agent: 2-10 parts; Dispersant: 1-10 parts; Water reducing agent: 0.1-1 part; Water-to-cement ratio: 0.23 to 0.38 parts.
2. The C7MS4-C5MS3 phosphate aluminate cement-based steel bar protective coating material according to claim 1, characterized in that: The inorganic gelling material comprises the following components in parts by weight: Aluminophosphate cement containing C7MS4-C5MS3 mineral phase: 65-85 parts; Sulphoaluminate cement: 5-10 parts; Portland cement: 20-30 parts.
3. The C7MS4-C5MS3 phosphate aluminate cement-based steel bar protective coating material according to claim 2, characterized in that: The aluminophosphate cement containing C7MS4-C5MS3 mineral phase comprises the following systems and components: Calcium phosphate aluminate C8A6P: 20-30%; Contains calcium aluminate phosphate C (A, P): 15-20%; Ca5(PO4)2SiO4: 20-25%; α-type Ca3(PO4)2: 1-10%; C4AF: 1-10%; C7MS4- C5MS3: 10-20%.
4. The C7MS4-C5MS3 phosphate aluminate cement-based steel bar protective coating material according to any one of claims 1 to 3, characterized in that: The C7MS4-C5MS3 mineral phase aluminophosphate cement comprises the following components: Fluorapatite: 15-20 parts: Low-grade bauxite: 30-50 parts; Low-grade limestone: 30-60 parts; Iron powder: 1-10 parts.
5. The C7MS4-C5MS3 phosphate aluminate cement-based steel bar protective coating material according to claim 1, characterized in that: The modulus of the binder is 1.0-10; the binder is composed of one or more of epoxy resin, styrene-butadiene latex, vinyl acetate and ethylene copolymer rubber powder; the emulsion stabilizer is composed of one or two of phenolic resin and coumarone resin.
6. The C7MS4-C5MS3 phosphate aluminate cement-based steel bar protective coating material according to claim 5, characterized in that: In the binder, the mass ratio of epoxy resin, styrene-butadiene latex, vinyl acetate and ethylene copolymer rubber powder is 10-20:70-80:1-10.
7. The C7MS4-C5MS3 phosphate aluminate cement-based steel bar protective coating material according to claim 1, characterized in that: The dispersant is composed of one or more of sulfonate, fatty alcohol polyoxyethylene ether and polyether polyol.
8. The C7MS4-C5MS3 phosphate aluminate cement-based steel bar protective coating material according to claim 1, characterized in that: The early strength agent is composed of one or more of sodium sulfate, triethanolamine, calcium formate and urea.
9. A method for preparing a C7MS4-C5MS3 phosphate aluminate cement-based steel bar protective coating material as claimed in any one of claims 1 to 8, characterized in that: The following steps are involved: 1) The fluorine-containing apatite, bauxite, low-grade limestone and iron powder are weighed, calcined at 1300-1500° C., rapidly cooled, crushed and sieved to obtain aluminophosphate cement containing C7MS4-C5MS3 mineral phases; 2) Mix the water reducing agent, dispersant, binder, early strength agent, emulsion stabilizer and water to obtain a mixed liquid; 3) Dry-mixing the inorganic gelling material; 4) Finally, the uniformly mixed inorganic gelling material and the mixed liquid are stirred thoroughly.
10. Use of the C7MS4-C5MS3 phosphate aluminate cement-based steel bar protective coating material as claimed in any one of claims 1 to 8 in steel bar rust prevention.
Citation Information
Patent Citations
Permeation type waterproof material for road engineering cement concrete structure
CN101786837A
Magnesium phosphate base reinforcing steel bar protective coating material and preparation method thereof
CN106116438A
Aluminophosphate cement-based steel bar-embedded material and preparation method thereof
CN106396604A
Phosphoaluminate cement-based rapid repairing material and preparation method thereof
CN106431153A
Steel cable anti-corrosion coating material as well as preparation method and application thereof
CN114873987A